The Influence of Brand Characteristic on Customer Brand Relationship Through Consumer Engagement as Mediator - Gustano, Yasmine Putri; Rubiyanti, Nurafni (SAFE-Network, 2023)
KRB.ID a knitwear business located in the Binong Jati knitting industry area, Indonesia. KRB.ID was established at the beginning of the COVID-19 pandemic and witnessed significant growth during this challenging period. Leveraging the expanding popularity of TikTok during the pandemic, KRB.ID used video content to raise brand awareness among TikTok users. Many of their videos gained visibility on TikTok's